In vitro activity of ceftazidime-avibactam and comparators against Enterobacterales and Pseudomonas aeruginosa isolates from Central Europe and Israel, 2014-2017 and 2018 - Kristóf, Katalin; Adámková, Václava; Adler, Amos; Gospodarek-Komkowska, Eugenia; Rafila, Alexandru; Billová, Sabina; Możejko-Pastewka, Barbara; Kiss, Ferenc (Diagnostic microbiology and infectious disease, 2021)
Between 2014 and 2017, 6,662 Enterobacterales and 1,953 P. aeruginosa isolates were collected by 19 centers in four central European countries and Israel. A further 2,585 Enterobacterales and 707 P. aeruginosa isolates were collected in 2018 by 28 centers in seven European countries and Israel as part of the Antimicrobial Testing Leadership and Surveillance (ATLAS) study. A central laboratory performed antimicrobial susceptibility testing using broth microdilution panels according to Clinical Laboratory Standards Institute (CLSI) guidelines. Susceptibility rates among Enterobacterales were highest to ceftazidime-avibactam (≥98.5%), colistin (≥97.3%), and meropenem (≥95.8%). Ceftazidime-resistant and multidrug-resistant (MDR) Enterobacterales subsets were highly susceptible to ceftazidime-avibactam (≥94.9%) and colistin (≥94.7%). Susceptibility rates to colistin among all P. aeruginosa were ≥97.4% and were ≥96.3% among ceftazidime-resistant and MDR subsets. Susceptibility rates to ceftazidime-avibactam were 91.9% (2014-2017), 86.3% (2018) and, in common with comparator agents, were lower among ceftazidime-resistant (≥51.7%) and MDR isolates (≥57.1%).
Keywords: Microbial Sensitivity Tests; ceftazidim; enterobakteriální infekce; Humans; fixní kombinace léků; beta-Lactamase Inhibitors; mikrobiální testy citlivosti; lidé; Enterobacteriaceae Infections; azabicyklické sloučeniny; antibakteriální látky; Europe; Enterobacteriaceae; Pseudomonas aeruginosa; Izrael; Pseudomonas Infections; Anti-Bacterial Agents; Drug Resistance, Bacterial; Ceftazidime; Azabicyclo Compounds; bakteriální léková rezistence; inhibitory beta-laktamasy; Drug Combinations; Israel; pseudomonádové infekce; Evropa